2017
DOI: 10.1007/s00294-017-0711-x
|View full text |Cite
|
Sign up to set email alerts
|

A mutated dph3 gene causes sensitivity of Schizosaccharomyces pombe cells to cytotoxic agents

Abstract: Dph3 is involved in diphthamide modification of the eukaryotic translation elongation factor eEF2 and in Elongator-mediated modifications of tRNAs, where a 5-methoxycarbonyl-methyl moiety is added to wobble uridines. Lack of such modifications affects protein synthesis due to inaccurate translation of mRNAs at ribosomes. We have discovered that integration of markers at the msh3 locus of Schizosaccharomyces pombe impaired the function of the nearby located dph3 gene. Such integrations rendered cells sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Diphthamide-eEF2 is thought to regulate protein translation by preventing ribosomal slippage and -1 frameshifting (32). This is in line with studies showing that loss of DPH3 results in decreased levels of the antiapoptotic protein XIAP via impairment of translation fidelity (33) and leads to enhanced sensitivity to cytotoxic agents (34). Regardless of the upstream cause of the increased priming we observe in BPDCN and AML cells, these data suggest that combinations of tagraxofusp with agents targeting BCL-2 or BCL-2 family members may be particularly active.…”
Section: Discussionsupporting
confidence: 70%
“…Diphthamide-eEF2 is thought to regulate protein translation by preventing ribosomal slippage and -1 frameshifting (32). This is in line with studies showing that loss of DPH3 results in decreased levels of the antiapoptotic protein XIAP via impairment of translation fidelity (33) and leads to enhanced sensitivity to cytotoxic agents (34). Regardless of the upstream cause of the increased priming we observe in BPDCN and AML cells, these data suggest that combinations of tagraxofusp with agents targeting BCL-2 or BCL-2 family members may be particularly active.…”
Section: Discussionsupporting
confidence: 70%
“…shown that sordarin resistance of yeast is significantly increased when the diphthamidation pathway is defective, as shown by genetic deletion one of the dph genes (Botet et al, 2008;Villahermosa et al, 2017). This outcome indicates that the diphthamide modification of eEF2, which is thought to be important for reading-frame maintenance on mRNA during translocation (Pellegrino et al, 2018), may probably allosterically cooperate with sordarin action; a lack of diphthamide abolishes sordarin sensitivity in fungal strains .…”
Section: Eef2-diphthamide Modificationmentioning
confidence: 96%
“…Besides, the Warburg effect, which refers to the reprogrammed energy metabolism in cancer cells, resembling the energy metabolism of highly proliferative yeast cells, constitutes a valuable opportunity in cancer research [30][31][32]. Consequently, the underlying mechanisms for cancer therapeutic candidates can be understood by using fission yeast as a eukaryotic unicellular cell death model [33][34][35].…”
Section: Introductionmentioning
confidence: 99%